2011
DOI: 10.1093/molbev/msr263
|View full text |Cite
|
Sign up to set email alerts
|

Role of Low-Complexity Sequences in the Formation of Novel Protein Coding Sequences

Abstract: Low-complexity sequences are extremely abundant in eukaryotic proteins for reasons that remain unclear. One hypothesis is that they contribute to the formation of novel coding sequences, facilitating the generation of novel protein functions. Here, we test this hypothesis by examining the content of low-complexity sequences in proteins of different age. We show that recently emerged proteins contain more low-complexity sequences than older proteins and that these sequences often form functional domains. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 29 publications
5
58
0
1
Order By: Relevance
“…The rapid expansion and contraction of repeating sequences suggests that they can contribute significantly to protein evolution and the generation of novel functional modules (4, 63, 74, 75). Within PfGARP, decreasing the number of repeating units within the N-terminal lysine-rich sequence proportionally decreases the efficiency of targeting.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid expansion and contraction of repeating sequences suggests that they can contribute significantly to protein evolution and the generation of novel functional modules (4, 63, 74, 75). Within PfGARP, decreasing the number of repeating units within the N-terminal lysine-rich sequence proportionally decreases the efficiency of targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, low-complexity region motifs have been shown to modulate protein-protein interactions. 35 Interestingly, JMJD5, a closely related family member which was previously shown to negatively regulate osteoclastogenesis and human circadian systems, was recently identified to regulate the nuclear translocation of PKM2 and thereby reprogramming HIF-1α-mediated glucose metabolism. 31,36,37 This regulation is consistent with our observation that JMJD8 is enhancing the metabolic activity of ECs by increasing the oxygen consumption and the maximal glycolytic function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that such segmental sequences occur in high abundance and unusual size and concur with palindromic sequences in proteins 39–41. The functional role of these segments has not been well understood; it has been speculated that using their ability to expand quickly in time, such abundance may potentiate into increased protein sequence space hence evolving into novel protein functions 39 40. Moreover, a possible role in evolutionary role has also been proposed 41.…”
Section: Discussionmentioning
confidence: 99%